Physiology of Angina and Its Alleviation With Nitroglycerin: Insights From Invasive Catheter Laboratory Measurements During Exercise. Issue 1 (4th July 2017) - Asrress, Kaleab N.; Williams, Rupert; Lockie, Timothy; Khawaja, Muhammed Z.; De Silva, Kalpa; Lumley, Matthew; Patterson, Tiffany; Arri, Satpal; Ihsan, Sana; Ellis, Howard; Guilcher, Antoine; Clapp, Brian; et al.
Abstract : Background: The mechanisms governing exercise-induced angina and its alleviation by the most commonly used antianginal drug, nitroglycerin, are incompletely understood. The purpose of this study was to develop a method by which the effects of antianginal drugs could be evaluated invasively during physiological exercise to gain further understanding of the clinical impact of angina and nitroglycerin. Methods: Forty patients (mean age, 65.2±7.6 years) with exertional angina and coronary artery disease underwent cardiac catheterization via radial access and performed incremental exercise using a supine cycle ergometer. As they developed limiting angina, sublingual nitroglycerin was administered to half the patients, and all patients continued to exercise for 2 minutes at the same workload. Throughout exercise, distal coronary pressure and flow velocity and central aortic pressure were recorded with sensor wires. Results: Patients continued to exercise after nitroglycerin administration with less ST-segment depression ( P =0.003) and therefore myocardial ischemia. Significant reductions in afterload (aortic pressure, P =0.030) and myocardial oxygen demand were seen (tension-time index, P =0.024; rate-pressure product, P =0.046), as well as an increase in myocardial oxygen supply (Buckberg index, P =0.017). Exercise reduced peripheral arterial wave reflection ( P <0.05), which was not further augmented by the administration of nitroglycerin ( P =0.648). The observed increases in coronary pressure gradient, stenosis resistance, and flow velocity did not reach statistical significance; however, the diastolic velocity–pressure gradient relation was consistent with a significant increase in relative stenosis severity (k coefficient, P <0.0001), in keeping with exercise-induced vasoconstriction of stenosed epicardial segments and dilatation of normal segments, with trends toward reversal with nitroglycerin. Conclusions: The catheterization laboratory protocol provides a model to study myocardial ischemia and the actions of novel and established antianginal drugs. Administration of nitroglycerin causes changes in the systemic and coronary circulation that combine to reduce myocardial oxygen demand and to increase supply, thereby attenuating exercise-induced ischemia. Designing antianginal therapies that exploit these mechanisms may provide new therapeutic strategies. Abstract : Supplemental Digital Content is available in the text.